Hubungan Antara Budaya Organisasi Dan Disiplin Dengan Produktivitas Mengajar Guru Sekolah Dasar Di Kecamatan Matraman Jakarta Timur - EE. Junaedi Sastradiharja; Nyai Fatimah (Al Ashriyyah, 2019)
This study aims to find out and test empirical data related to the relationship between organizational culture, discipline and teacher teaching productivity simultaneously or separately. In this study, the authors used a survey method with a correlational and regression approach to quantitative data obtained from the object of research, namely Private Primary School teachers in Matraman sub-district. The sample of this study was 93 respondents out of a total of 120 private elementary school teacher populations in Matraman District in the odd semester of the 2018/2019 academic year. Data collection is done by using questionnaire / questionnaire, observation, and documentation techniques. The type of analysis used is correlation analysis and descriptive described regression. The results of this study are: First, there is a positive, strong and significant relationship between organizational culture and teacher teaching productivity with a correlation coefficient (r) of 0.751 and a coefficient of determination (R2) of 56.4%. The direction of influence is indicated by the regression equation Ŷ = 31,073 + 0.749 X1, it can be read that each increase in one unit score of organizational culture (X1) affects the increase in teacher teaching productivity score (Y) of 0.749 points. Second, there is a positive, strong and significant relationship between discipline and teacher teaching productivity with a correlation coefficient (r) of 0.736 and a coefficient of determination (R2) of 54.2%. The direction of influence is indicated by the regression equation Ŷ = 31,073 + 0,749 X2, it can be read that each increase in one unit of discipline score (X2) affects the increase in the teacher's teaching productivity score (Y) by 0.749 points. Third, there is a positive, strong and significant relationship between organizational culture and simultaneous discipline with teacher teaching productivity. The correlation coefficient (r) is 0.815 and the coefficient of determination (R2) is 66.4%. The direction of influence is indicated by the regression equation Ŷ = 12,191 + 0,467 X1 + 0,427 X2. From this equation it can be read that each increase in one independent unit score of organizational culture and discipline jointly affects the increase in teaching productivity scores 0.894.